COVID‐19 and entrepreneurship: Future research directions - Ratten, Vanessa (Strategic Change, 2021)
Innovation and futuristic thinking are needed to derive better policies to address the COVID‐19 pandemic. Policy considerations in terms of entrepreneurship will help understand the importance of future research on digital transformation, leadership, business impact, and social inclusiveness. The societal shifts due to COVID‐19 impacts unveil opportunities for entrepreneurial adjustments to achieve competitiveness and growth.